Utilizing Student Socio-coordinated Mimicry: Complex Movement Conversations in Physical Education. Issue 3 (3rd July 2018) - Rhoades, Jesse Lee; Hopper, Timothy Frank
ABSTRACT: This article explores Complexity Theory and applications of nonlinear dynamics in physical education (PE). The authors of this article discuss Complexity Theory and its applications to students and student learning. Additionally, there will be discussion of how the networking learning process associated with socio-coordinated mimicry creates a "movement conversation" between learners rooted in the relational complexity of students within a PE lesson. Finally, the authors discuss research opportunities within PE, allowing for a close collaboration between pedagogical researchers and biomechanists to examine the emergent qualities within the "movement conversations" between students. Overall, this article seeks to illustrate the possibilities of utilizing Complexity Theory within PE pedagogy and research.